2020
DOI: 10.1177/1524838020916837
|View full text |Cite
|
Sign up to set email alerts
|

The Neglect of Left-Behind Children in China: A Meta-Analysis

Abstract: Objective: To evaluate the neglect of left-behind children (LBC) in China. Method: Participants: Children separated from one or both parents for at least 6 months. Intervention: Trauma of separation. Comparison: Non-left-behind children (NLBC). Outcomes: Neglect rates and severity. Only case–control studies were included. Results: Thirteen studies were included; there were 18,688 LBC in a large sample ( N = 42,003) of children aged 0–18 years in China. The overall neglect rate was significantly higher in LBC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…From a personal point of view, they need more time to do what they want to do. Previous studies have found that parental migration has many negative effects on left-behind children, such as social anxiety, depression, learning counseling and inadequate supervision [31,32]. These problems bring obstacles to the work of raising grandchildren.…”
Section: Discussionmentioning
confidence: 99%
“…From a personal point of view, they need more time to do what they want to do. Previous studies have found that parental migration has many negative effects on left-behind children, such as social anxiety, depression, learning counseling and inadequate supervision [31,32]. These problems bring obstacles to the work of raising grandchildren.…”
Section: Discussionmentioning
confidence: 99%
“…The equity issue of using the smartphone app as a primary intervention tool is also a concern that might limit the generalizability of mHealth programs ( 36 , 37 ). The left-behind children usually live with their grandparents and suffer from multiple neglects compared with their peers ( 38 ). This study also indicates that the left-behind children do not have adequate access and support for using smartphone apps for online health education.…”
Section: Discussionmentioning
confidence: 99%
“…This study also indicates that the left-behind children do not have adequate access and support for using smartphone apps for online health education. The national monitoring data of migrant workers indicated that 30.1% of migrant workers left their children at home ( 38 ). This issue of left-behind children should be taken into consideration when promoting this program on a broader scale.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, left-behind children are a special group of children living in rural China whose parents have migrated to cities in search of work (22). Parentchild separation has been associated with a range of negative long-term physical and mental health outcomes, although many studies of children who are separated from parents involve the compounding traumatic exposure of war (23)(24)(25). The issues related to left-behind children have aroused widespread concern in Chinese society currently (26).…”
Section: Introductionmentioning
confidence: 99%